Designing a Fiscal Framework for a Prospective Commodity Producer : Options for Lebanon - Jarmuzek, Mariusz (IMF Working Papers; Working Paper ;, 2014)
Lebanon is expected to have gas resources in its Mediterranean basin, and these could turn the country into a natural gas producer over the next decade. Lebanon's economy and institutions will thus need to adapt to the challenges and opportunities that such change will bring. In this paper, we address how Lebanon's fiscal framework will need to be reformulated to take into account potential resource revenue. Designing a fiscal regime appropriately is an absolute prerequisite to make sure the government can receive a fair share of the resources while investors face appropriate incentives to invest and develop the sector. This step should be followed by setting macro-fiscal anchors and supporting institutions. The prospective framework should initially be focused on ensuring fiscal sustainability and intergenerational equity, given the estimated relatively short horizon of Lebanon's gas resources. Strong institutional arrangements also need to underpin the prospective framework, to ensure that the pace of resource wealth's use is set in line with Lebanon's capacity constraints.